Quality Tourism as Soft Power: A Political Economy Comparison of Singapore and Bali - Fiya Ainur Rohmatika (Department of International Relations, Brawijaya University, 2026)
The recovery of global tourism after the COVID-19 pandemic shows increasingly strategic dynamics, especially in Southeast Asia, which now positions tourism as an instrument of soft power and regional economic and political competitiveness. This study stems from the need to understand how two key destinations (Singapore and Bali) implement quality tourism to project cultural influence and strengthen their economic structures. Specifically, this study examines how Singapore, which in 2024 received 16.5 million international tourists (a 21% increase from 2023) with tourism revenues of S22.4 billion in the January–September 2024, successfully consolidated a state-led quality tourism model through premium services, global connectivity, and the hosting of high-profile international events that reinforced the city-state's image as a cultural and economic hub in Asia. In contrast, Bali demonstrated a culture-driven soft power model rooted in cultural richness, spirituality, and natural landscapes. In 2024, Bali generated Rp107 trillion in foreign exchange, or 44% of Indonesia's total tourism foreign exchange, making it the primary national tourism engine. Despite receiving millions of domestic and international tourists each year, its economic value stems not only from volume but also from increased value creation through the accommodation, culinary, transportation, and creative industries. Comparative findings show that the effectiveness of quality tourism as a soft power strategy is greatly influenced by destination management capacity: Singapore excels through institutional stability and service consistency, while Bali faces challenges related to overtourism and environmental sustainability. This study concludes that quality tourism has the potential to become a powerful instrument of regional diplomacy if supported by sustainable governance, quality tourism experiences, and a balance between economic growth and cultural preservation.